An iodine mass-balance for Lake Constance, Germany: Insights into iodine speciation changes and fluxes - Gilfedder, Benjamin Silas; Petri, M.; Wessels, Martin; Biester, Harald (Geochimica et cosmochimica acta, 2010)
Lake Constance is one of Europe’s largest oligotrophic lakes and provides a water source for more than 4.5 million people in Germany and Switzerland. We present here a 12month study on iodine concentrations, speciation and fluxes to and from the lake to gain a quantitative understanding of the limnic iodine cycle. Monthly water samples were obtained from all major tributaries (14) and the outflow to construct a mass-balance model. Sediment traps were also deployed in the lake for two years at two different stations. Total soluble iodine (TSI) in aqueous samples were analysed by ICP-MS and speciation (iodide, iodate and soluble organically bound iodine, SOI) by ion chromatography-ICP-MS. Iodine concentrations in the Alpine tributaries (1-2μgl−1) decreased over the summer months due to increasing proportions of snow and glacial melt water from the Alps, while iodine levels in the lowland rivers (∼2-10μgl−1) increased over the summer. Deposition of TSI to the catchment (16,340kg I yr−1) was similar to the TSI out-flux by rivers (16,000kg I yr−1). By also including the particulate riverine iodine flux out of the catchment (∼12,350kg I yr−1) it is shown that the catchment is a net source of iodine, with the highest particulate fluxes coming from the Alpine rivers. The total TSI flux to the lake was 16,770kg I yr−1, the largest proportion coming from the Alpenrhein (43%), followed by the Schussen (8%) and Bregenzer Ach (7.7%). Overall the mass-balance for TSI in the lake was negative, with more iodine flowing out of the lake than in (−2050kg I yr−1; 12% of TSI in-flux). To maintain mass-balance, 8.8μg I m−2 d−1 from the Obersee and 23μg I m−2d−1 from the Untersee must be released from the sediments into the water column. Thus, in comparison with the total iodine flux to the sediments measured by the sediment traps (4762-8075kg I yr−1), up to 39% of the deposited iodine may be mobilised back into the lake. SOI was the dominant iodine fraction entering the lake, with a total flux of 10,290kg I yr−1 (64% of TSI input), followed by iodate (3120kg I yr−1) and iodide (2760kg I yr−1). Net formation of SOI from iodide and iodate was also noted within the lake, with an estimated production of 6560kg I yr−1, suggesting a strong role for biology in iodine cycling. In conclusion, organically bound iodine was the dominant iodine species in aqueous and solid phases in Lake Constance, despite low DOC concentrations (<2mgl−1), and thus is expected to play an important role in iodine cycling in most freshwater environments.
Gesehen am 22.03.2023